Analysis of Varicose Vein in Lower Extremities Risk Factors on Woman Laborers of Tobacco Picker at Ajung District Jember Regency - Muhammad Faizal Akbar; Ida Srisurani Wiji Astuti; Desie Dwi Wisudanti (Faculty of Medicine, University of Jember, 2019)
Varicose vein (VV) in lower extremities are common diseases in the clinic but there is little concern from clinicians as they are considered mild and low mortality. The complications of VV can be ulcers or worst like Congestive Heart Failure (CHF). Several risk factors that can affect the occurrence of VV are women, age, long standing, overweight, pregnancy multiparity, and hormonal contraception. The general purpose of this research is knowing the relationship between risk factors mentioned above and the prevalence of VV on female laborers of tobacco picker at Ajung District Jember District. This research use observational analytic method with cross sectional study design to 72 people who meet the inclusion criteria by purposive sampling method. The sample were given questionnaire, informed consent, then measured by weight scales and microtoise staturemeter. The diagnosis of VV was obtained from the photos that been consulted to cardiothoracic surgeon at dr. Soebandi Hospital Jember. The result of contingency coefficient C correlation test said that only age has significant relation to VV occurrence states (p = 0,044; r = 0,231; OR = 3,053), while others are not significant (p> 0,05 and r < 0.2). The conclusion of this study is that only the age factor has a statistically significant relationship and the positive correlation with the weak correlation to the occurrence of lower extremities VV on woman laborers of the tobacco picker of Ajung District, Jember Regency. Keywords: Varicose Vein, Lower Extremities